Satan Says - Olds, Sharon ((Pitt Poetry Series))
Sharon Olds (San Francisco 1942) obtuvo el Lamont Award from the Academy of American Poets y el National Book Critics Circle Award. Algunas de sus obras son: Satan Says; The Wellspring; The Dead and the Living.